(untitled) (Proceedings of Voronezh State University. Series: Geology, 2024)
Introduction: Strontium minerals of the epidote group, niigataite and epidote-(Sr), were discovered relatively recently and are still quite rare minerals, so their study is an urgent task. In this article, we describe the discovery of niigataite and epidote-(Sr) in rodingites of the Bazhenovsky ophiolite massif in the Middle Urals (Russia). Methodology: For the study, electron probe microanalysis, X-ray diffractometry and X-ray fluorescence methods were used. The chemical composition of minerals was studied on a CAMECA SX 100 electron probe microanalyzer with five wave spectrometers and using standard samples of reference metals (IGG Ural Branch RAS, Yekaterinburg). The chemical composition of rodingite was determined using an XRF 1800 X-ray fluorescence wave spectrometer from Shimadzu (IGG Ural Branch RAS). X-ray studies of minerals were carried out using a DRON-2.0 X-ray diffractometer at the Ural State Mining University (Yekaterinburg). Results and discussion: Strontium minerals of the epidote group are established in vein dikes, up to 0.5 m thick, cutting serpentinized harzburgite. According to its chemical composition, the dike belongs to the group of lamprophyres. The mineral composition of the rock is as follows: phlogopite, clinochlore, antigorite, diopside, vesuvianite, titanite, calcite, hydroxylapatite and kimrite. Ore minerals include chalcocite and gold. Epidote-(Sr) and niigataite form joint fine-grained whitish accumulations in the rock matrix, up to 1−2 mm in size. In the center of the clusters, niigataite with the empirical formula (Ca1.44Sr0.59)Σ2.03(Al2.50Fe0.47Mg0.01)Σ2.98[(Si2.98Ti0.01)Σ2.99O12](OH) is noted, and in the middle the edges – epidote-(Sr) with the empirical formula (Ca1.34Sr0.68)Σ2.02(Al2.29Fe0.70Mg0.01)Σ3.00[(Si2.97Ti0.01)Σ2.98O12](OH). In this case, the latter quantitatively predominates. The belonging of minerals to the epidote group is confirmed by X-ray phase analysis. Conclusion: For the first time in Russia, within the Bazhenov ophiolite massif, rare minerals of the epidote group – niigataite and epidote-(Sr) – have been identified. Moreover, the discovery of niigataite is the third in the world, after two finds in Japan. Both minerals were found in a rodingite paragenesis formed along a substrate of alkaline ultrabasic rock – a lamprophyre dike. The minerals are associated with relict phlogopite and newly formed aggregates of vesuvianite, diopside and chlorite.